Bichectomy and its contribution to facial harmony - Cesar Augusto Daher Ceva Faria; Ronan Caputi Silva Dias; Amanda Costa Campos; José Carlos Daher; Rafael Sabino Caetano Costa; Leonardo David Pires Barcelos (Revista Brasileira de Cirurgia Plástica)
Introduction: Buccal fat removal was described for the first time by Heister in 1732. In 1802, Bichat identified the adipose nature of this tissue. There is a close association between buccal fat and masticatory muscles, which helps infants suck owing to the sliding motion of the tissues. Its prominence diminishes with age, both through modest reduction in volume and facial growth. Bichectomy or bichatectomy is a surgical procedure that involves extraction of Bichat's fat pad for aesthetic and/or functional purposes. This study aimed to show that bichectomy is a low-risk surgical procedure with good results, provided it is appropriately indicated and is performed following technical standards according to the anatomy of the facial structures. Methods: This prospective cohort study was conducted between January 2016 and April 2018 and included 59 patients with a mean age of 31 years. The follow-up time was 12-26 months. Results: Of 59 patients, 46 were female, and 13 were male. All patients underwent same-day surgery. On average, 3.2 mL of fat was removed. Conclusion: Removal of Bichat's fat according to anatomical principles is safe. This technique can improve facial harmony. Success depends on application of appropriate techniques.